Queue Model Analysis At Lawson Minimarket Jatinangor - Desty Hapsari Kirana; Dzulfikar Hibatulaziz; Hafizhan Dhifan Fadhillah (CV Putra Publisher, 2025)
Lawson is a popular minimarket offering ready-to-eat food and beverages, making it a frequent destination for customers in the Jatinangor area. Due to the high volume of visits, the efficiency of its service system plays a vital role in ensuring customer satisfaction. This study aims to analyze the performance of the queueing system at Lawson Jatinangor using a descriptive quantitative approach based on direct observation of customer arrival and service times. The collected data were processed using the POM-QM software through the waiting line module. The results show that the queueing system operates with high efficiency, characterized by a short average waiting time, a low number of customers in the queue, and a low cashier utilization rate. The high probability of the system being idle indicates underutilized service capacity. The study concludes that while Lawson’s current service system is responsive, there is still potential to improve operational efficiency by adjusting the number of active cashiers during peak hours